(untitled) (INNOVATIVE ECONOMY, 2020)
Kostetskyi V.V., Butov A.M. MANAGEMENT OF FINANCIAL FLOWS OF ENTERPRISES FROM THE STANDPOINT OF FINANCIAL LOGISTICS Purpose. The aim of the article is to substantiate the peculiarities of the modern paradigm of financial management of enterprises on the basis of a combination of fundamental principles and models of financial management and logistics, which will promote self-organization of optimization and security processes in the management of financial flows of business entities. Methodology of research. A set of general scientific and special methods of economic research are used in the process of research, in particular: the abstract and logical method – in formulating the conclusions of the research results; the method of analogy and comparison – when studying the practice of financial management and logistics management of financial flows; the method of theoretical generalization is used in carrying out a critical analysis of the results of research by domestic and foreign scientists in relation to issues related to the management of financial flows in the context of the logistic concept of the enterprise. Findings. It is substantiated that it is necessary to take into account the peculiarities of implementation and improvement of management of financial flows of enterprises in order to solve the existing problems with creating an effective mechanism for managing financial flows. It is proposed to develop methodological approaches to the management of financial flows, which should be based on nonlinear dynamic modeling and non-deterministic forecasting mode. It was considered expedient to develop a new target financial model of the enterprise aimed at synchronization and balance of financial and related flows, which in general would ensure harmonization of interests not only of enterprises but also of all interested persons. It is revealed that the financial approach to management of financial flows acquires new specific features due to the use of logistic approach and transforms into logistics and oriented. Originality. The influence of logistics on the processes of financial management of enterprises is substantiated and methodological and methodical aspects for successful implementation of management of financial flows in logistic systems of enterprises are determined. Practical value. The obtained results deepen the practical principles of institutional support for the development of financial logistics at the enterprise and facilitate the search for new opportunities for efficient management of financial flows within the existing logistics chains, and will provide greater flexibility and adaptability of enterprises to an overly changing environment. Key words: financial management; financial flows; logistics; financial logistics; management of financial flows.